1998
DOI: 10.1111/j.1532-5415.1998.tb01039.x
|View full text |Cite
|
Sign up to set email alerts
|

Barriers to Obtaining Consent in Dementia Research: Implications for Surrogate Decision‐Making

Abstract: Absence of functional surrogate decision-makers is a major barrier to research and clinical decision-making for hospitalized patients with advanced dementia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
31
0
2

Year Published

1999
1999
2021
2021

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 40 publications
(33 citation statements)
references
References 12 publications
0
31
0
2
Order By: Relevance
“…As previously reported, very few surroforgo certain treatments among the intervention gates approached for consent refused to enroll the groups. It is possible that larger numbers might patient in the study (12). have revealed differences in certain categories.…”
Section: Resultsmentioning
confidence: 94%
“…As previously reported, very few surroforgo certain treatments among the intervention gates approached for consent refused to enroll the groups. It is possible that larger numbers might patient in the study (12). have revealed differences in certain categories.…”
Section: Resultsmentioning
confidence: 94%
“…Third, another potential problem that may be mitigated with a family decision-making approach is that designated surrogates for dementia patients may need assistance to serve adequately in this role (Baskin et al, 1998). Prior research has shown that, even when patients are fully capacitous, the assistance of a close relative or friend can help the patient better understand the medical options available (Frost, 1975).…”
Section: Rationale For Including Family Membersmentioning
confidence: 98%
“…Who that person should be is a vital question, which has been much debated in the literature. A family member is assumed to have the best knowledge of the patient's preferences and values earlier in life but is not always available or willing to participate (Baskin et al, 1998). Various reasons have been reported for giving informed consent, such as hope of direct or indirect benefits, desperation, trust in the investigator, belief in the goodness of research, and altruism (Sugarman et a]., In Sweden, a vulnerable person may be under the protection of a legal representative whose primary role is to see to the person's best interests, in particular his/her financial affairs, but has no authority by law to give approval for participation in research.…”
Section: Selection Of Proxy Decision-makersmentioning
confidence: 99%